The Influence of Price Perception and Electronic Word of Mouth on Purchase Intentions for Vans Shoes - Robbyllah Maulana Muslikh,; Endah Budiarti , (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to determine and analyze the influence of price perception and electronic word of mouth (eWOM) on the purchase intention of Vans shoes. The research uses a quantitative method and involves 100 respondents who are students of 17 August University Surabaya 1945 and have purchased or own Vans shoes. Data analysis was conducted using SPSS 25. The results of the study indicate that price perception has a significant impact on the purchase intention of Vans shoes, electronic word of mouth (eWOM) affects purchase intention, and both price perception and electronic word of mouth (eWOM) together influence the purchase intention of Vans shoes.